2017
DOI: 10.33834/bkr.v2i2.77
|View full text |Cite
|
Sign up to set email alerts
|

Capital Flows to BRICS Countries during 2000-2010

Abstract: The objective of this paper is to analyze the dynamics of financial flows towards the BRICS in the period 2000-2010. Particularly, the paper examines the impacts of the capital controls adopted by each economy on the movements of specific types of capital registered in their financial accounts. The idea is to show that, regarding financial dynamics, the economies of the BRICS present peculiar characteristics that should be taken into account in the formulation of strategies for global financial regulation. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Korinek and Sandri [23] analyzed both the macro-prudential regulation and capital control being ideally adjusted to mitigate the risks to financial stability in emerging economies based on data from East Asian countries. Munhoz et al [24] applied Generalized Autoregressive Conditional Heteroscedasticity models (GARCH) to study the volatility of banks across Brazil, Russia, India, and China (BRIC) countries with the objective of discovering how prudential capital regulations contributed to financial stability. Their empirical analysis showed that capital www.videleaf.com flow instability is less affected in countries that adopted capital control regulation of Basel Accords.…”
Section: Literature Review Empirical Evidence On Risk-based Capital A...mentioning
confidence: 99%
“…Korinek and Sandri [23] analyzed both the macro-prudential regulation and capital control being ideally adjusted to mitigate the risks to financial stability in emerging economies based on data from East Asian countries. Munhoz et al [24] applied Generalized Autoregressive Conditional Heteroscedasticity models (GARCH) to study the volatility of banks across Brazil, Russia, India, and China (BRIC) countries with the objective of discovering how prudential capital regulations contributed to financial stability. Their empirical analysis showed that capital www.videleaf.com flow instability is less affected in countries that adopted capital control regulation of Basel Accords.…”
Section: Literature Review Empirical Evidence On Risk-based Capital A...mentioning
confidence: 99%
“…Korinek and Sandri (2016) analyzed both the macro-prudential regulation and capital control being ideally adjusted to mitigate the risks to financial stability in emerging economies based on data from East Asian countries. Munhoz et al (2017) applied Generalized Autoregressive Conditional Heteroscedasticity models (GARCH) to study the volatility of banks across Brazil, Russia, India, and China (BRIC) countries with the objective of discovering how prudential capital regulations contributed to financial stability. Their empirical analysis showed that capital flow instability is less affected in countries that adopted capital control regulation of Basel Accords.…”
Section: Empirical Evidence On Risk-based Capital Adequacy Requirement and Bank Risk Associationmentioning
confidence: 99%